Salib Kampung sebagai Simbol Inkulturasi: Integrasi Keimanan Katolik dan Ritual Adat Nosu Minu Podi - Pirminus Pirminus; Tjang, Yanto Sandy; Amadi Amadi; Hemma Gregorius Tinenti; Felisitas Yuswanto (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study explores the Village Cross as a symbol of inculturation, integrating Catholic faith with the Nosu Minu Podi ritual in Dusun Perintis, Balai Sebut Village, Sanggau Regency. Nosu Minu Podi, a post-harvest rice ritual, originally centered on the ancestral statue (Pantak) as the main focus of worship. The introduction of Catholicism led to a symbolic transformation, replacing the Pantak with the Village Cross while maintaining ancestral values and harmonizing them with Catholic practices. This research uses a qualitative approach combining ethnography and contextual theology. Data were collected through participatory observation, semi-structured interviews, and field documentation. Findings reveal that the Village Cross serves dual functions: as a religious symbol affirming God’s presence and spiritual protection, and as a marker of social and cultural identity. This transformation strengthens community solidarity, preserves traditional practices, and provides a medium for faith formation among youth. The study highlights that inculturation enables the integration of local traditions with religious teachings, creating space for contextual, inclusive, and practical pastoral approaches. It contributes to scholarly understanding of the interplay between religion, culture, and community identity, emphasizing the enduring relevance of local wisdom in contemporary religious practice.